THE EFFECT OF STUDENTS’ PERFORMANCE IN JUNIOR SECONDARY MATHEMATICS ON THEIR PERFORMANCE IN, SENIOR SECONDARY MATHEMATICS, FURTHER-MATHEMATICS, AND PHYSICS - Ifamuyiwa, A. S. (Sokoto Educational Review, 2020)
This study examined the extent to which students’ performance in JSS Mathematics would correlate with and predict performance in SSS Mathematics, Further-Mathematics and Physics. Gender effects on the students ’ performance in each of the subjects were also investigated. 288 senior secondary school students, selected from 4 public secondary schools in Eti-Osa Local Government Area of Lagos State using purposive sampling technique, participated in the study. Students ’ JSCE and SSCE results for the years 2002 - 2005 in the subjects were the instruments. Results showed that students’ performance in JSS Mathematics related significantly, highly and positively with performance in Physics (r = 0.77), SSS Mathematics (r = 0.75) and Further-Mathematics (r = 0.72). The study discovered that performance in JSS Mathematics contributed significantly to the students ’ performance at SSS level, accounting for 59%, 52% and 56% o f the variance in the students’ performance in Physics, Further-Mathematics and SSS Mathematics respectively. The study also found a significant gender difference in the performance o f students in SSS Mathematics in favour o f the mate students but found no significant difference between the performance o f male and female students in JSS Mathematics, SSS Further-Mathematics and SSS Physics. The implications o f the study fo r refocusing research and evaluation in Science, Technology, and Mathematics (STM) Education were dismissed.